Identification and functional analysis of shared gene signatures between systemic lupus erythematosus and Sjögren's syndrome. Issue 3 (7th September 2022) - Gao, Zhaowei; Yang, Lan; Liu, Chong; Wang, Xi; Zhang, Huizhong; Dong, Ke
Abstract: Background: Systemic lupus erythematosus (SLE) is an autoimmune disease that can affect multiple systems. Sjögren's syndrome (SS) is an autoimmune disease that may be primary SS (pSS) or occur together with other autoimmune diseases, including SLE. This study aimed to explore the shared gene signatures in SLE and pSS. Methods: Gene expression data sets of SLE (GSE50772 and GSE81622) and pSS (GSE84844 and GSE48378) were obtained and analyzed for differentially expressed genes (DEGs) in peripheral blood mononuclear cells (PBMCs). A protein–protein interaction (PPI) network was constructed. Gene ontology (GO) and KEGG pathway enrichment analysis were carried out for the DEGs. Results: We screened 232 and 110 DEGs from the SLE and pSS data sets, respectively. We found 32 shared DEGs, which were all upregulated in patients compared with controls. Among these 32 DEGs, 11 genes showed a more than twofold change in all data sets ( IFI27, IFI44L, RSAD2, IFIT1, IFI44, USP18, IFI6, HERC5, EPSTI1, OAS1, and OAS3 ). PPI analysis showed that 29 genes interacted with each other. GO analysis showed that these 32 shared DEGs were mainly enriched in biological processes associated with the type I interferon signaling pathway, defense response to viruses, response to viruses, negative regulation of viral genome replication, and the immune response. Kyoto Encyclopedia of Genes and Genomes pathway analysis showed that these 32 DEGs were related to virus infection. Conclusion: This study showed that alterations to biological processes associated with the response to virus infection play critical roles in both SLE and pSS. Abstract : Thirty‐two shared differential expressed genes (DEGs) were screened in systemic lupus erythematosus and Sjögren's syndrome transcriptome data sets. These 32 shared DEGs were mainly enrichment in biological progress associated with type I interferon signaling pathway, defense response to virus, response to virus, negative regulation of viral genome replication, and immune response. Key points: Two hundred and thirty‐two and 110 differentially expressed genes (DEGs) were screened in systemic lupus erythematosus (SLE) and primary Sjögren's syndrome (pSS) peripheral blood mononuclear cells RNA‐seq data sets, respectively. Thirty‐two shared DEGs were screened in SLE and pSS data sets, which were all upregulated in patients compared to controls. These 32 shared DEGs were mainly enrichment in biological progress associated with type I interferon signaling pathway, defense response to virus, response to virus, negative regulation of viral genome replication, and immune response.